TINJAUAN TENTANG BUDAYA ISLAM DI TANAH JAWA BERDASARKAN DALIL-DALIL PEMAHAMAN IMAM SYAFIâI - , Amir Syarifuddin, Muhammad Hatta Mustafa (PARENTAL, 2014)
ABSTRACT The Islamic tradition which becom the part of islamic life in our Countri, especially in Java island, rather had shake-up, this problem caused by the enternity of the other culture to Indonesia that influence the understanding to each others. The reality insociety shows that islamic tradition which is maintained can limit the negatif effecct of foreign culture which entered, especially western. The reflection of Yasin and others epistle in Al Qurâan and tahlil, tasbih, tahmid, shalawat and other dzikir is a part that can be separated from islamic culture and java culture. All of them is reflected from society that still combine between culture and religion, it can be understood from ruwah culture(ngirim arwah)/ziarah, yassinan culture, dzikir culture, and others. It is can not be separated from islamic daâwah that spread by wali songo that acculturated the culture, so it is easy to be understood by the society especially Java society. Key Words : Yassin, Thahlil, pilgrimege entombment, the mixture of culture. Â